EULAR evidence‐based recommendations on the management of systemic glucocorticoid therapy in rheumatic diseases - Hoes, J N (BMJ Group, 2007)
OBJECTIVE: To develop evidence‐based recommendations for the management of systemic glucocorticoid (GC) therapy in rheumatic diseases. METHODS: The multidisciplinary guideline development group from 11 European countries, Canada and the USA consisted of 15 rheumatologists, 1 internist, 1 rheumatologist–epidemiologist, 1 health professional, 1 patient and 1 research fellow. The Delphi method was used to agree on 10 key propositions related to the safe use of GCs. A systematic literature search of PUBMED, EMBASE, CINAHL, and Cochrane Library was then used to identify the best available research evidence to support each of the 10 propositions. The strength of recommendation was given according to research evidence, clinical expertise and perceived patient preference. RESULTS: The 10 propositions were generated through three Delphi rounds and included patient education, risk factors, adverse effects, concomitant therapy (ie, non‐steroidal anti‐inflammatory drugs, gastroprotection and cyclo‐oxygenase‐2 selective inhibitors, calcium and vitamin D, bisphosphonates) and special safety advice (ie, adrenal insufficiency, pregnancy, growth impairment). CONCLUSION: Ten key recommendations for the management of systemic GC‐therapy were formulated using a combination of systematically retrieved research evidence and expert consensus. There are areas of importance that have little evidence (ie, dosing and tapering strategies, timing, risk factors and monitoring for adverse effects, perioperative GC‐replacement) and need further research; therefore also a research agenda was composed.